Partikel Fatis Bahasa Mandarin dalam Drama Televisi: Kajian Awal terhadap Partikel Le - Hasanah, Hana Nurul (Paradigma: Jurnal Kajian Budaya, 2023)
One of the characteristics of non-standard language varieties is employing phatic particles in the beginning of the sentence, in the middle or in the end of it. In Mandarin language, one phatic particle that is commonly used by Mandarin speakers is le particle. This research generally aimed at describing the functions of phatic particle le found in television drama series. The series from which the data were gathered is Zan Jia Na Xie Shir, the first part from the first episode. From 78 phatic particles found in the drama series, of which 47 of them are le as phatic particle; 10 of them are distributed in the middle of the sentence and 37 of them are distributed in the end of the sentence. Based on the result, the function of “le” in the middle of the sentence is starting a new talk and maintaining a talk. Meanwhile, the function of “le” in the end of the sentence is maintaining a talk and ending a talk. Therefore, it seemed that the function of le as phatic particle tend to not inline with its distribution in the sentence.